Genetic effects on white matter integrity in drug-naive patients with major depressive disorder: a diffusion tensor imaging study of 17 genetic loci associated with depressive symptoms - Kakeda, Shingo (Neuropsychiatr Dis Treat, 2019)
BACKGROUND: A genome-wide association study using megadata identified 17 single-nucleotide polymorphisms (SNPs) in candidate genes for major depressive disorder (MDD). These MDD susceptibility polymorphisms may affect white matter (WM) integrity. This study aimed to investigate the relationship between WM alterations and 17 SNPs in candidate genes for MDD in the first depressive episode of drug-naive MDD patients using a tract-based spatial statistics (TBSS) method. METHODS: Thirty-five drug-naive MDD patients with a first depressive episode and 47 age-and sex-matched healthy subjects underwent diffusion tensor imaging scans and genotyping. The genotype–diagnosis interactions related to WM integrity were evaluated using TBSS for the 17 SNPs. RESULTS: For the anterior thalamic radiation, cingulum, corticospinal tract, inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, superior longitudinal fasciculus, uncinate fasciculus, forceps major, and forceps minor, the genotype effect significantly differed between diagnosis groups (P<0.05, family-wise error corrected) in only one SNP, rs301806, in the arginine–glutamic acid dipeptide (RE) repeats (RERE) gene. CONCLUSION: The RERE polymorphism was associated with WM alterations in first-episode and drug-naive MDD patients, which may be at least partially related to the manifestation of MDD. Future studies are needed to explore the gene–environment interactions with regard to individual WM integrity.